Civil service management in developing countries: what works?: evidence from a survey with 23,000 civil servants in Africa, Asia, Eastn Europe and Latin America - Meyer-Sahling, Jan-Hinrik; Schuster, Christian; Sass Mikkelsen, Kim
Civil servants are central to effective governance in developing countries. They deliver essential services to citizens, commission infrastructure, regulate economic activity and engage in diplomacy with foreign countries – to name just a few tasks. This puts a premium on understanding how to manage civil servants in developing countries effectively. Yet, to-date, there are scarcely any quantitative studies which deliver robust findings across developing countries – let alone regions – on what works in civil service management. To address this gap, this report draws on data from an original survey of 23,000 civil servants in ten countries in Africa, Asia, Eastern Europe and Latin America – the, to our knowledge, largest original cross-country survey of civil servants ever conducted in the developing world.